Case study of air distribution of the hospital operating room in Malaysia / Dng Lai Chet - Dng, Lai Chet (2012)
In a hot and humid country, Malaysia shows the highest percentage of surgical site infection in comparison with other healthcare associated infections. The design of operating rooms is significantly different from on-site surveys on numbers of operating rooms (ORs) in Malaysia. To date, investigation on air distribution in OR is limited in developing country. Computer Fluid Dynamics (CFD) was used in this research for further study in purpose to analyze the air flow features in ORs. In current study, two ORs, namely Sarawak General Hospital Heart Centre OT-5 and University of Malaya Medical Centre OT-11 with different design features were studied. In the first case study, there were fieldwork measurement and simulation study at Sarawak General Hospital Heart Centre, which includes the study of comparison of the potential of reducing air flow rate. Then, the case study was continued with fieldwork measurement and simulation study at University of Malaya Medical Centre (UMMC). OT-11 of UMMC designed with up to 14 air inlets and 3 air outlets. The airflow features for such design will be analyzed. Since an OR needs to fulfill the requirement of a Class 7 clean room according to ISO 14644-1, hence the design of the array of inlets were studied through a comparison of 1 x 4 and 2 x 2 inlet array. It was found that, 1 x 4 inlet array performs better than 2 x 2 inlet array. In the last part of this work, the study on the effect of maldistribution of air velocities was also included by using a 2-D CFD simulation.